Feeding ecology of chimpanzees (Pan troglodytes verus) inhabiting a forest‐mangrove‐savanna‐agricultural matrix at Caiquene‐Cadique, Cantanhez National Park, Guinea‐Bissau. Issue 6 (19th March 2015) - Bessa, Joana; Sousa, Cláudia; Hockings, Kimberley J.
<x xml:space="preserve">Abstract</x> With rising conversion of "natural" habitat to other land use such as agriculture, nonhuman primates are increasingly exploiting areas influenced by people and their activities. Despite the conservation importance of understanding the ways in which primates modify their behavior to human pressures, data are lacking, even for well‐studied species. Using systematically collected data (fecal samples, feeding traces, and direct observations), we examined the diet and feeding strategies of an unhabituated chimpanzee community (Pan troglodytes verus) at Caiquene‐Cadique in Guinea‐Bissau that inhabit a forest‐savanna‐mangrove‐agricultural mosaic. The chimpanzees experienced marked seasonal variations in the availability of plant foods, but maintained a high proportion of ripe fruit in the diet across months. Certain wild species were identified as important to this community including oil‐palm (Elaeis guineensis) fruit and flower. Honey was frequently consumed but no other insects or vertebrates were confirmed to be eaten by this community. However, we provide indirect evidence of possible smashing and consumption of giant African snails (Achatina sp.) by chimpanzees at this site. Caiquene‐Cadique chimpanzees were confirmed to feed on nine different agricultural crops, which represented 13.6% of all plant species consumed. Consumption of fruit and nonfruit crops was regular, but did not increase during periods of wild fruit scarcity. Crop consumption is an increasing and potentially problematic behavior, which can impact local people's tolerance toward wildlife. To maximize the potential success of any human–wildlife coexistence strategy (e.g., to reduce primate crop feeding), knowledge of primate behavior, as well as multifaceted social dimensions of interactions, is critical. Am. J. Primatol. 77:651–665, 2015. © 2015 Wiley Periodicals, Inc.